Community annoyance from aircraft induced noise in Delhi - SANYOGITA, SANYOGITA; KUMAR, Krishan; JAIN, V. K. (Archives of Acoustics, 2007)
Air traffic noise is a major cause of community annoyance in the residential areas near airports. The present study has been prompted by the need to examine the noise levels induced by the increased air traffic in Delhi in recent years. Noise levels have been measured in the indoor environment of two prominent residential areas of Delhi, namely, University Campus (UC) and Vasant Vihar (VV) which lie underneath the landing flight path of aircraft in Delhi. Spectral distributions show higher noise levels at lower frequencies and exhibit a declining trend with increase in frequency. With the help of spectral information, an index of aircraft noise, PNdB (perceived noise levels in decibels) is determined to assess relative annoyance or noisiness felt by the community of residential areas. PNdB values in the case of UC vary from a minimum of 66.7 to a maximum of 85.2. Further down the landing path, PNdB levels at VV are found to be appreciably higher in the range of 76.18-91.37. Results of social survey conducted to assess the community response to aircraft noise reveal that a majority (73%) of the respondents experience moderate to extreme annoyance. This is in conformity with the rather high PNdB values obtained for both the residential areas.